Mathematical Literacy Ability And Self-Efficacy Students In Search Solve Create And Share (SSCS) Learning With Contextual Approaches - Lestari, Dewi Indah; Waluya, S B; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2020)
The objectives of this study are to test the quality of SSCS learning with a contextual approach and describe the mathematical literacy skill in terms of students’ self-efficacy levels. This research was a type of mixed quantitative and qualitative research. This research was conducted at State Senior High School 1 Kendal in the academic year of 2015/2016. The research subjects were X grade students consisting of one experimental class with the SSCS learning treatment with a contextual approach and one control class. In the experimental class, it was chosen 2 students in the high, medium, and low categories based on students’ self-efficacy. Testing the quality of learning was seen from 3 stages, namely the stages of planning, implementation, and assessment. The results were obtained that SSCS learning with contextual approach is in good quality. Students with high categories for high self-efficacy and low self-efficacy can fulfill the seven components of mathematics literacy well. Students with categorization for high self-efficacy and low self-efficacy are able to fulfill the six components of mathematics literacy well but they are still lacking in the reasoning and argument components. Students with low categories for high or low self-efficacy both have good skills in the communication component but are lacking in the other six components of mathematical literacy.